An N-Gram Based Method for Bengali Keyphrase Extraction - Sarkar, Kamal (Information Systems for Indian Languages, 2011)
Keyphrases provide the subject metadata that gives the clues about the content of a document. In this paper, we present a new method for Bengali keyphrase extraction. The proposed method has several steps such as extraction of n-grams, identification of candidate keyphrases and assigning scores to the candidate keyphrases. Since Bengali is a highly inflectional language, we have developed a lightweight stemmer for stemming the candidate keyphrases. The proposed method has been tested on a collection of Bengali documents selected from a Bengali corpus downloadable from TDIL website.